Hubungan Pemerintahan Antara Pemerintah Pusat dan Pemerintah Daerah Serta Peran Wakil Pemerintah - Hanif Nurcholis (Jurnal Studi Pemerintahan, 2011)
The local government is part of a national government empowered to regulate and administer governmental affairs entrusted to her. Therefore, between central and local governments have a systemic relationship between sub-systems so as to form an integral system of government. The relationship between central and local governments is determined in its oversight system that rests on two bases: hierarchical and functional. Base hierarchy to determine the extent to which higher authority overseeing the local government while the functional basis to determine the extent to which functional departments / sectoral and local government departments overseeing general. Based on this surveillance pattern then there are four models of relationships referred to by the countries in this world with many variants. Four models are models of French, British model, German model, and model of the Soviet Union. Indonesia's New Order embraced the French model, while at the Reformation Orde more embracing German model.